Studying Cosmopolitanism in a Globalized World - Anna Khalonina (Migrating Minds)
Review article - Cosmopolitanism in Hard Times, ed. by Vincenzo Cicchelli and Sylvie Mesure. Leiden: Brill, 2020, 406 p., ISBN: 978-90-04-43801-9 Globalisation de la culture, ed. by Vincenzo Cicchelli and Sylvie Octobre. Réseaux 226-227. Paris: La découverte, 2021, 300 p., ISBN : 978-2-348-06945-1 Youth on Edge: Facing Global Crises in Multicultural French Society, by Vincenzo Cicchelli and Sylvie Octobre, translated by Sarah-Louise Raillard. London: Palgrave Macmillan, 2022, 253 p., ISBN: 978-3-031-11824-1